Path diversity reception employing steering vector arrays and sequence estimation techniques for ISI channels. - Fujii, M. (IEEE Journal on selected areas in communications)
We propose a path diversity reception technique that uses steering vector arrays and Viterbi algorithm-based sequence estimation techniques to cope with severe intersymbol interference (ISI). The proposed scheme suppresses some delayed paths with spatial and temporal processing based on the single constraint sample matrix inversion algorithm to reduce excess ISI for sequence estimation. The path diversity branches are weighted in proportion to the quality of the array output signals and then combined via the branch-metric-combining (BMC) Viterbi algorithm to estimate the most likely transmitted sequence. Maximum likelihood sequence estimation, limited-state sequence estimation, and decision-feedback sequence estimation are examined for their suitability as estimation techniques. Consequently, the proposed scheme is sufficient for managing various kinds of channel models. Thus, the proposed scheme is suitable for high-speed time-division multiple access (TDMA) mobile radio systems, because, in this kind of transmission, fading can be presumed to be nearly quasi-static during the burst, and the delayed paths are spread over several symbols